Abnormal retinal development associated with FRMD7 mutations. (31st March 2014) - Thomas, Mervyn G.; Crosier, Moira; Lindsay, Susan; Kumar, Anil; Araki, Masasuke; Leroy, Bart P.; McLean, Rebecca J.; Sheth, Viral; Maconachie, Gail; Thomas, Shery; Moore, Anthony T.; Gottlob, Irene
Abstract : Idiopathic infantile nystagmus (IIN) is a genetically heterogeneous disorder, often associated with FRMD7 mutations. As the appearance of the retina is reported to be normal based on conventional fundus photography, IIN is postulated to arise from abnormal cortical development. To determine whether the afferent visual system is involved in FRMD7 mutations, we performed in situ hybridization studies in human embryonic and fetal stages (35 days post-ovulation to 9 weeks post-conception). We show a dynamic retinal expression pattern of FRMD7 during development. We observe expression within the outer neuroblastic layer, then in the inner neuroblastic layer and at 9 weeks post-conception a bilaminar expression pattern. Expression was also noted within the developing optic stalk and optic disk. We identified a large cohort of IIN patients ( n = 100), and performed sequence analysis which revealed 45 patients with FRMD7 mutations. Patients with FRMD7 mutations underwent detailed retinal imaging studies using ultrahigh-resolution optical coherence tomography. The tomograms were compared with a control cohort ( n = 60). The foveal pit was significantly shallower in FRMD7 patients ( P < 0.0001). The optic nerve head morphology was abnormal with significantly decreased optic disk area, retinal nerve fiber layer thickness, cup area and cup depth in FRMD7 patients ( P < 0.0001). This study shows for the first time that abnormal afferent system development is associated with FRMD7 mutations and could be an important etiological factor in the development of nystagmus.